Volumetria, biomassa e qualidade da madeira de Hymenaea courbaril L. proveniente de plantios na Amazônia Central - (:unkn) unknown (Universidade Federal do Amazonas, 2016)
This study aimed to adjust mathematical models to estimate the commercial volume with bark and dry biomass, and assess the quality of wood jatobá (Hymenaea courbaril L.) from plantations Embrapa Western Amazon, at different ages. For volumetric analysis was performed 100% inventory and cubage of 10 trees with 17 years and 12 to 24, 10 being adjusted models for estimating the volume. For quantification of biomass was used for each planting trees 10, and the adjustment of the equation 9 were tested models. The quality of the wood was evaluated through the application of physical tests (humidity, basic density and dimensional stability) and mechanical (parallel compression, bending and Janka hardness), governed by the ABNT 7190 (1997) and ASTM D 143-94 (2000), in specimens taken from five trees each planting. The statistics used for comparisons took into account average, confidence interval, variance, standard deviation and coefficient of variation. For verification of statistical difference between the properties t test was applied with p <0.05. The equation obtained best fit to estimate the volume was V = -0.362 + 0.028 .d + 0.00769 . h, and an estimated air dry biomass, ln (MS) = -2.209 + 1.859. In (d) + 0.753. ln (h). The adjusted determination coefficients showed values greater than 89% and equal error estimation standards to 0.061 and 0.172 respectively. The average increase of the trade volume estimated was considered low, 11.79 m³/ha/year and 11.13 m³/ha/year for trees of 17 and 24 years respectively. The estimate of biomass found was 207.71 Mg/ha for planting with 17 years and 280.71 Mg/ha for planting with 24 years. Regarding the quality of the wood, it not had evidence that age influenced the tested properties. However the results demonstrate the potential to replace some traditional species of the market, with approximate physical characteristics of jatobá from native forests, and mechanical resistance often superior to other commercial woods. Thus, except for use in heavy construction (structural), wood jatobá up to 24 years can be used for making various products which are not subjected to high compressive stresses parallel to the fibers.
Keywords: Povoamento florestal; Biomassa; Madeira de Jatobá; Jatobá (Hymenaea courbaril L.); Volumetria; CIÊNCIAS AGRÁRIAS: RECURSOS FLORESTAIS E ENGENHARIA FLORESTAL